2017
DOI: 10.18805/lr.v0i0.7598
|View full text |Cite
|
Sign up to set email alerts
|

Seed quality behavior of Soybean (Glycine max) as influenced by different packaging materials and storage conditions

Abstract: A Study was carried out to find out the seed quality behavior of soybean (Glycine max) as influenced by different packaging materials and storage conditions. Soybean seeds were stored in different packaging materials viz., gunny bags, high density polythene bags and vacuum packed bags stored at room temperature (25 ± 2º C) and cold storage (4 ± 1º C) for a period of 18 months. The treatments having six combinations and consisting of different containers viz., gunny bags, high density polythene bags and vacuum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…It was noticed that PLV has less volatility for O2 and SMC during the storage periods than WPP and HDPE, resulting in low seed activity and maintenance of seed vigor. This result was similar to the finding of Abreu et al [29] in sunflower seeds and Meena et al [30] in soybean seeds.…”
Section: Effects Of Storage Period Storage Condition and Packaging Ty...supporting
confidence: 92%
See 1 more Smart Citation
“…It was noticed that PLV has less volatility for O2 and SMC during the storage periods than WPP and HDPE, resulting in low seed activity and maintenance of seed vigor. This result was similar to the finding of Abreu et al [29] in sunflower seeds and Meena et al [30] in soybean seeds.…”
Section: Effects Of Storage Period Storage Condition and Packaging Ty...supporting
confidence: 92%
“…According to Azadi and Younesi [40], sorghum seeds stored at room temperature showed reduced GI as the temperature and RH increased. Consistent with study of Meena et al [30], vacuum-packing groundnut seeds had a minimum decline in the seedling vigor index when compared with gunny bags and HDPE.…”
Section: Effects Of Storage Period Storage Condition and Packaging Ty...supporting
confidence: 88%
“…Singh and Dadlani (2003) also opined that the germination per cent was affected by packaging materials during storage. Meena et al (2017) also observed that seeds stored in vacuum packed bags maintained the seed quality with least deterioration with respect to all the seed quality parameters compared to seeds stored in gunny bags and high density polythene bags. Chin and Kieu (2006) concluded that hermetically sealed storage system using poly-ethylene bag reduced insect population in the stock of rice seeds and increases germination percentage of rice seeds as compared to the traditional method of aerobic storage by farmers.…”
Section: Seed Germinationmentioning
confidence: 67%
“…Higher seed viability and vigour were maintained with modified atmospheric storage particularly in carbon dioxide and vacuum packaged condition. The probable reason for differences in longevity of seeds in the modified atmospheric storage conditions might be due to the variation in the gas concentrations, where the treatments C 2 and vaccum packing having gas combination of higher CO 2 with zero per cent of oxygen concentration i.e., low oxygen atmosphere and also the seeds stored under vacuum condition showed better germination as reported by Meena et al (2017). W hereas, germination was reported to decrease in peas with increase in oxygen level (Roberts and Abdalla, 1968).…”
Section: Influence Of Modified Gaseous On Seed Quality In Kabuli Chic...mentioning
confidence: 91%